1975
DOI: 10.1017/s0043174500062755
|View full text |Cite
|
Sign up to set email alerts
|

Germination Behavior of Florida Pusley Seeds. I. Effects of Storage, Light, Temperature and Planting Depths on Germination

Abstract: Freshly harvested Florida pusley (Richardia scabraL.) seeds do not germinate in continuous dark, but do germinate if exposed to more than 2 hr of light each day. Increasing periods of illumination up to 16 hr per day increases the germination percentages. Scarification increases the rate of germination in the presence of light. Scarification also causes germination of seeds stored for 8 months or longer in total darkness. The seeds fail to germinate at constant temperatures of 15 C or less and at 40 C. Almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 4 publications
3
23
1
Order By: Relevance
“…The emergence of the F. miliacea weed seedlings decreased with the increasing planting depth. Similar results were observed by Biswas et al . (1975).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The emergence of the F. miliacea weed seedlings decreased with the increasing planting depth. Similar results were observed by Biswas et al . (1975).…”
Section: Resultssupporting
confidence: 92%
“…The emergence of the F. miliacea weed seedlings decreased with the increasing planting depth. Similar results were observed by Biswas et al (1975). It was stated that Florida Pusley failed to emerge where seeds were buried to a depth of ≥ 1.5 cm.…”
Section: Experiments 1: Effect Of Sowing Depth On the Emergence Of Fimsupporting
confidence: 83%
“…Germination studies with annual weeds typically result in 80±90% total germination (Biswas et al, 1975;Weaver et al, 1988;Harvey & Forcella, 1993); much higher than the emergence rates observed in this study. Low rates of germination that are often observed with perennial weeds have been attributed to their ability to reproduce by vegetative means in stable plant communities (Harper, 1977).…”
Section: Resultscontrasting
confidence: 57%
“…No germination was observed at 10 or 15 C; however, there was 5% germination at 17 C. High temperatures ($ 35 C) cause a pronounced reduction in germination, similar to that found in many other weed species. For example, false broomweed (Ericameria austrotexana M. C. Johnston) germinated maximum at 20 to 25 C and declined above and below this temperature with no germination at 5 or 40 C (Biswas et al 1975). Bur cucumber (Sicyos angulatus L.) seed germination was reduced severely at temperatures below 20 C and above 30 C (Mann et al 1981).…”
Section: Resultsmentioning
confidence: 99%
“…Temperature, moisture, light, and pH requirements for germination vary considerably, depending on the weed species (Elberlein 1987;Evetts and Burnside 1972;Jain and Singh 1989;Singh and Achhireddy 1984). Some weed species can emerge from a wide range of planting depth, but others must be close to the soil surface (Biswas et al 1975;Reddy and Singh 1992;Wilson 1979).…”
mentioning
confidence: 99%